A review on chemical and biological properties of Cayratia trifolia Linn. (Vitaceae) - Kumar, Dinesh; Kumar, Sunil; Gupta, Jyoti; Arya, Renu; Gupta, Ankit (Pharmacognosy Reviews, 2011)
Cayratia trifolia Linn. Domin Syn. Vitis trifolia (Family: Vitaceae) is commonly known as Fox grape in English; Amlabel, Ramchana in Hindi and Amlavetash in Sanskrit. It is native to India, Asia and Australia. It is a perennial climber having trifoliated leaves with 2-3 cm long petioles and ovate to oblong-ovate leaflets. Flowers are small greenish white and brown in color. Fruits are fleshy, juicy, dark purple or black, nearly spherical, about 1 cm in diameter. It is found throughout the hills in India. This perennial climber is also found in the hotter part of India from Jammu and Rajasthan to Assam extending into the peninusular India upto 600 m height. Whole plant of Cayratia trifolia has been reported to contain yellow waxy oil, steroids/terpenoids, flavonoids, tannins upon preliminary phytochemical screening. Leaves contain stilbenes (piceid, reveratrol, viniferin, ampelopsin). Stem, leaves, roots are reported to possess hydrocyanic acid, delphinidin and several flavonoids such as cyanidin is reported in the leaves. This plant also contains kaempferol, myricetin, quercetin, triterpenes and epifriedelanol. Infusion of seeds along with extract of tubers is traditionally given orally to diabetic patients to check sugar level of blood. Paste of tuberous is applied on the affected part in the treatment of snake bite. Whole plant is used as diuretic, in tumors, neuralgia and splenopathy. Its climbers wrapped around the neck of frantic bullock and poultice of leaves are used to yoke sores of bullock. The bark extract shows the antiviral, antibacterial, antiprotozoal, hypoglycemic, anticancer and diuretic activity. This article focuses on the upgraded review on chemical and biological properties of Cayratia trifolia Linn. and triggers further investigation on this plant.
Keywords: Biological; Cayratia trifolia; chemical; review